SN2016coi (ASASSN-16fp): An Energetic H-stripped Core-collapse Supernova from a Massive Stellar Progenitor with Large Mass Loss - Terreran G (IOP PUBLISHING LTD, 2025)
We present comprehensive observations and analysis of the energetic H-stripped SN 2016coi (a.k.a. ASASSN-16fp), spanning the gamma-ray through optical and radio wavelengths, acquired within the first hours to similar to 420 days post explosion. Our observational campaign confirms the identification of He in the supernova (SN) ejecta, which we interpret to be caused by a larger mixing of Ni into the outer ejecta layers. By modeling the broad bolometric light curve, we derive a large ejecta-mass-to-kinetic-energy ratio (M-ej similar to 4-7 M-circle dot, E-k similar to (7-8) x 10(51) erg). The small [Ca II] lambda lambda 7291,7324 to [O I] lambda lambda 6300,6364 ratio (similar to 0.2) observed in our late-time optical spectra is suggestive of a large progenitor core mass at the time of collapse. We find that SN 2016coi is a luminous source of X-rays (L-X > 10(39) erg s(-1) in the first similar to 100 days post explosion) and radio emission (L-8.5 (GHz) similar to 7 x 10(27) erg s(-1) Hz(-1) at peak). These values are in line with those of relativistic SNe (2009bb, 2012ap). However, for SN 2016coi, we infer substantial pre-explosion progenitor mass loss with a rate (M)over dot similar to (1-2) x 10(-4) M-circle dot yr(-1) and a sub-relativistic shock velocity v(sh) similar to 0.15c, which is in stark contrast with relativistic SNe and similar to normal SNe. Finally, we find no evidence for a SN-associated shock breakout gamma-ray pulse with energy E-gamma > 2 x 10(46) erg. While we cannot exclude the presence of a companion in a binary system, taken together, our findings are consistent with a massive single-star progenitor that experienced large mass loss in the years leading up to core collapse, but was unable to achieve complete stripping of its outer layers before explosion.